The Effect of Cordia Myxa L. on Storage Quality of Vitis Vinifera - Zainab Ali; Hamza Hamza; Sara Shareef; Ahmed Shaker; Sayed Razavi; Muntaha Yousief (International Journal of Nutrition Sciences, 2025)
Background: Fruits have a limited short life due to chemical changes and microbial damages. This study was conducted to determine the effect of Cordia myxa L. on storage quality of Vitis vinifera.Methods: The grape fruits of V. vinifera L. were dipped with 1% and 2% of C. myxa L. extract (CME). The fruits were then packed in 250 g plastic containers and stored in a refrigerated incubator at ±4°C. The weight loss, acidity, total soluble solids (TSS), and damages were assessed in addition to sensory evaluation that was undertaken during 6weeks storage period.Results: A good response was demonstrated by treatment with CME, while dipping with 2% of CME was superior based on less weight loss that happened during storage (0.076), together with an increased acidity and TSS and the lowest percentage of microbial damages when compared to other treatments. A significant positive correlation coefficient (≤0.01) was seen between TSS and acidity and damaged fruits. The correlation was negative between acidity, damage, and TSS and weight. The sensoryevaluation revealed a good quality for fruit dipped with 2% of CME.Conclusion: The importance of immersing grape fruits with CME was demonstrated to extend the storage quality; while the fruits retained their nutritional and sensory values too.